Concentration of phenolic compounds from apple pomace extracts by nanofiltration at lab and pilot scale with a techno‐economic assessment. (29th September 2017) - Uyttebroek, Maarten; Vandezande, Pieter; Van Dael, Miet; Vloemans, Sam; Noten, Bart; Bongers, Bas; Porto‐Carrero, Wim; Muñiz Unamunzaga, Maria; Bulut, Metin; Lemmens, Bert
Abstract: Apple pomace can be used as resource for the extraction of phenolic compounds with antioxidant properties. Pressing of apple in juice and pomace at lab scale in open air (aerobic) and under N2 atmosphere (anaerobic) showed a recovery of phenolic compounds of 85% in juice and pomace after anaerobic pressing, compared to 43% after aerobic pressing, indicating loss of phenolic compounds by oxidation and the advantage of anaerobic over aerobic pressing. After a membrane screening and concentration test at lab scale, the commercial nanofiltration membrane NFX was selected to concentrate phenolic compounds in an ethanol : water extract of apple pomace. At pilot scale, the concencentration of 10 selected phenolic compounds and quinic acid increased from 59.5 mg/L in the ethanol : water extract to 1256.1 mg/L in the final retentate, that is, by a factor 21.1. The volume of the crude extract was reduced by a factor of 28.5 during the filtration, indicating some loss of phenolic compounds during pilot testing due to membrane fouling or oxidation of polyphenols. The pilot concentration test using a spiral‐wound membrane module showed good flux and concentration of phenolic compounds, indicating the technical feasibility of membrane technology for efficient concentration of polyphenols in an ethanol : water extraction solvent. Unfortunately, the extraction and concentration process was not economically feasible under the assumptions made. Practical applications: The valorization of food waste for the production of high‐added value products is an increasingly hot topic. Phytochemicals are present in relatively low concentration in the fruit matrix, and concentration in the extraction solvent is necessary to develop an industrially relevant process. In this study, membrane filtration was selected for concentration due to its low energy consumption and mild processing conditions compared to other technologies. Membrane screening and testing at lab and pilot scale with techno‐economic assessment can be used by food and nutraceutical industries to evaluate membrane technology for concentration of phytochemicals extracted from agroindustrial by‐products.